2012
DOI: 10.1016/j.regsciurbeco.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, migrants' education and immigration policy: Theory and evidence from bilateral data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…This shows that Pakistani migrants send more remittances when the economic conditions improve at home, which supports the portfolio investment motive. This result is consistent with the findings in Kock andSun (2011), Lueth andArranz (2008), and Docquier et al (2012). However, remittance flows to Pakistan do not seem to respond to the host country's economic conditions.…”
Section: Empirical Findingssupporting
confidence: 91%
“…This shows that Pakistani migrants send more remittances when the economic conditions improve at home, which supports the portfolio investment motive. This result is consistent with the findings in Kock andSun (2011), Lueth andArranz (2008), and Docquier et al (2012). However, remittance flows to Pakistan do not seem to respond to the host country's economic conditions.…”
Section: Empirical Findingssupporting
confidence: 91%
“…On the other hand, Faini (2007) suggest that high-skilled migrant's send fewer remittances. Docquier et al (2012) argue that skilled migrant's send more remittances in the presence of more restrictive immigration policies. Unfortunately, in this study, we are unable to use data at a disaggregated level, both on type and skill level of migration, because the data are not available for bilateral flows.…”
Section: 1-data and Variable Descriptionmentioning
confidence: 99%
“…Furthermore, remittances managed to improve the infant mortality rate and life expectancy (Zhunio et al, 2012:4610). However, Docquier et al (2012) observed that remittances had a more positive influence on education in the receiving country if the immigration policy in the destination country is restrictive and vice-versa.…”
Section: Review Of Related Literaturementioning
confidence: 96%